Investigating the effects of multiplicative white noise on solitons in birefringent fibers through the perturbed Kundu-Eckhaus equation with high dispersion - Zayed, E. M. E.; Gepreel, K. A.; El-Horbaty, M.; Hashemi, M. S.; Arnous, A. H.; Secer, A.; Ozisik, M.; Bayram, M. (INDIAN ASSOC CULTIVATION SCIENCE, 2025)
The study of highly dispersive optical solitons in birefringent fibers is crucial for advancing high-speed optical communication and nonlinear fiber optics. In this research, we analyze the properties of such solitons by employing the eighth-order nonlinear perturbed Kundu-Eckhaus equation, incorporating multiplicative white noise in the It & ocirc; sense. To this end, we apply three robust analytical methods: the addendum to Kudryashov's method, the unified Riccati equation expansion method, and the addendum to the modified sub-ODE method. These techniques enable the derivation of explicit solutions relevant to various physical and engineering problems. Our analysis reveals multiple soliton solutions, including Jacobi elliptic solutions, bright solitons, straddled solitary solutions, singular solitons, and Weierstrass elliptic functions. The findings significantly contribute to the understanding of nonlinear optical pulse propagation in birefringent fibers, potentially enhancing the design and optimization of advanced optical communication systems. These results offer deeper insight into soliton dynamics and provide new perspectives on practical applications in fiber optics and nonlinear wave theory.
Keywords: Riccati equation; Kudryashov; Sub-ODE method; Solitons; Kundu-Eckhaus equation; OPTICAL SOLITONS; PARABOLIC LAW; Physics